Experimental Attempts at and Theoretical Study of the Thermal Generation of o-Carborane-Supported N-Heterocyclic Carbenes - Mei-Juan Liang; Ke-Cheng Chen; Zhongzheng Cui; Yan-Chang Zhou; Yan Wang; Fan Qi; Xu-Qiong Xiao (Inorganics)
N-Heterocyclic carbenes (NHCs) have been widely utilized over the past three decades due to their broad applications, yet synthetic methods for their preparation remain limited. A promising approach for NHC generation involves the thermolysis of NHC adducts. Herein, we report the synthesis of NHC pentafluorobenzene adducts featuring an o-carboranyl group in the backbone (2), which, unlike previously studied systems, resists thermal decomposition. Density functional theory (DFT) calculations were used to investigate the discrepancy, revealing that the decomposition reaction is kinetically controlled. For widely studied NHC systems like IMes and SIMes, the activation barriers were calculated to be 246.3 kJ/mol and 267.3 kJ/mol, respectively, aligning with reactions requiring heating. In contrast, the o-carborane system exhibited a significantly higher barrier of 320.5 kJ/mol, primarily due to the structural influence of the o-carborane backbone. Further analysis indicates that delocalization of π-electrons from the backbone into the NHC’s p-orbitals lowers the activation barrier, whereas delocalization into an exo-NHC ring increases it. These findings provide new insights into the thermal generation of NHCs and we hope it can offer guidance for future NHC design and synthesis.